Peluang dan Tantangan Dakwah Halaqah Dalam Membangun Karakter Santri Pondok Pesantren - Irma Irma; Taufik Pelu; Ahmad Syaekhu (Jurnal Keislaman, 2023)
Islamic boarding schools for centuries have succeeded in creating a superior generation with a strong religious character. Islamic values are integrated into every interaction between a murabbi and a santri. This study aims to describe the opportunities and challenges of implementing halaqah da'wah and building the religious and honest character of the students. This study uses a descriptive qualitative research type, with the main data sources being students as informants, murabbi as key informants, and the foundation chairman as extending informants. Documents, journals, and books become secondary data. data collection with in-depth interview techniques, observation, and documentation. Data analysis was carried out using technique: data reduction, presentation, and conclusion drawing. The results showed that the opportunities and challenges were not only felt by the students; the murabbi and the boarding school also felt them. Santri has the opportunity to add additional insight related to adab and religious aqidah. Integrating Islamic values through halaqah da'wah is an alternative solution for learning models in public schools so that the values of the younger generation are not distorted by the times. On the other hand, the challenges in the form of feeling tired and sleepy after activities reduce their concentration when implementing halaqah da'wah. The results of this study become a reference for the pesantren in arranging an efficient schedule for implementing halaqah da'wah.